Dynamic imperfections in the Compact Linear Collider - Gohil, C (2020)
The Compact Linear Collider (CLIC) is a proposed TeV-scale electron-positron collider under development at the European Organization for Nuclear Research (CERN). CLIC adopts a staged approach with three centre-of-mass energies: 380 GeV, 1.5 TeV and 3 TeV. This work focuses on the first stage, which has been optimised for studies of the Higgs boson and top-quark physics.